Are neurological and psychiatric disorders different?. (November 2015) - David, Anthony S.; Nicholson, Timothy
Summary: There have been recent calls to abandon the distinction between neurological and psychiatric disorders on philosophical and moral grounds. Crossley and colleagues, in this issue, meta-analyse published structural brain imaging data and prove that they are different after all – or do they?